A follow-up study on the recovery and reinfection of Omicron COVID-19 patients in Shanghai, China - Mengna Lin; Kangli Cao; Feixiang Xu; Xueling Wu; Yao Shen; Su Lu; Zhongshu Kuang; Hailin Ding; Shuyun Yuan; Mian Shao; Guorong Gu; Lingyu Xing; et al. (Emerging Microbes and Infections, 2023)
Limited follow-up data is available on the recovery of Omicron COVID-19 patients after acute illness. It is also critical to understand persistence of neutralizing antibody (NAb) and of T-cell mediated immunity and the role of hybrid immunity in preventing SARS-CoV-2 reinfection. This prospective cohort study included Omicron COVID-19 individuals from April to June 2022 in Shanghai, China, during a large epidemic caused by the Omicron BA.2 variant. A total of 8945 patients from three medical centres were included in the follow up programme from November 2022 to February 2023. Of 6412 individuals enrolled for the long COVID analysis, 605 (9.4%) individuals experienced at least one sequelae, mainly had fatigue and mental symptoms specific to Omicron BA.2 infection compared with other common respiratory tract infections. During the second-visit, 548 (12.1%) cases of Omicron reinfection were identified. Hybrid immunity with full and booster vaccination had reduced risk of SARS-CoV-2 reinfection by 0.29-fold (95% CI: 0.63–0.81) and 0.23-fold (95% CI: 0.68–0.87), respectively. For 469 participants willing to the hospital during the first visit, those who received full (72 [IQR, 36–156]) or booster (64 [IQR, 28–132]) vaccination had significantly higher neutralizing antibody titers than those with incomplete vaccination (36 [IQR, 16–79]). Moreover, non-reinfection cases had higher neutralizing antibody titers (64 [IQR, 28–152]) compared to reinfection cases (32 [IQR, 20–69]).